P16INK4a Regulates ROS-Related Autophagy and CDK4/6-Mediated Proliferation: A New Target of Myocardial Regeneration Therapy. (18th February 2023) - Sun, Jiateng; Zhou, Liuhua; Yang, Tongtong; Deng, Bo; Bao, Yulin; Gu, Lingfeng; Wang, Hao; Wang, Liansheng
Abstract : Neonatal mice achieve complete cardiac repair through endogenous myocardial regeneration after apical resection (AR), but this capacity is rapidly lost 7 days after birth. As an upstream inhibitor of cyclin-dependent kinase 4/6- (CDK4/6-) mediated cell cycle activity, p16 INK4a is widely involved in regulating tumor and senescence. Given that p16 INK4a had a significant negative regulation on cell proliferation, targeting cardiomyocytes (CMs) to inhibit p16 INK4a seems to be a promising attempt at myocardial regeneration therapy. The p16 INK4a expression was upregulated during perimyocardial regeneration time. Knockdown of p16 INK4a stimulated CM proliferation, while p16 INK4a overexpression had the opposite effect. In addition, p16 INK4a knockdown prolonged the proliferation time window of newborn myocardium. And p16 INK4a overexpression inhibited cell cycle activity and deteriorated myocardial regeneration after AR. The quantitative proteomic analysis showed that p16 INK4a knockdown mediated the cell cycle progression and intervened in energy metabolism homeostasis. Mechanistically, overexpression of p16 INK4a causes abnormal accumulation of reactive oxygen species (ROS) to induce autophagy, while scavenging ROS with N-acetylcysteine can alleviate autophagy and regulate p16 INK4a, CDK4/6, and CyclinD1 in a covering manner. And the effect of inhibiting the proliferation of p16 INK4a -activated CMs was significantly blocked by the CDK4/6 inhibitor Palbociclib. In summary, p16 INK4a regulated CM proliferation progression through CDK4/6 and ROS-related autophagy to jointly affect myocardial regeneration repair. Our study revealed that p16 INK4a might be a potential therapeutic target for myocardial regeneration after injury.